Effect of Jetty to the Capacity of Bogowonto River Mouth, Kulon Progo Daerah Istimewa Yogyakarta - Muhammad Dandy Kusuma; Mohammad Bagus Adityawan; Ana Nurganah Chaidar (Institut Teknologi Bandung, 2023)
Abstract. Bogowonto River is the main river in the Bogowonto watershed which is included in the Serayu Bogowonto River Area. In the dry season, the mouth of the Bogowonto river closes because sediment deposits accumulate at the river mouth, disrupting the river flow to the sea. At high tide, sediment holds the Bogowonto River flow because it impacts the backwater downstream of the Bogowonto river, causing flooding in several locations, especially around Yogyakarta International Airport. The flow capacity of the Bogowonto river is decreasing, causing flooding problems, so this study needs to do an analysis. Backwater analysis at the Bogowonto River estuary simulates the existing jetty in the HEC-RAS program. In contrast, simulated morphology change river was with two jetty scenarios using the DELFT3D program. Keywords: Sediment, flooding, backwater, estuary, jetty. Abstrak. Sungai Bogowonto merupakan sungai utama di DAS Bogowonto yang termasuk dalam Wilayah Sungai Serayu Bogowonto. Pada musim kemarau muara sungai Bogowonto menutup karena endapan sedimen menumpuk di muara sungai sehingga mengganggu aliran sungai ke laut. Pada saat pasang, sedimen menahan aliran Sungai Bogowonto karena berdampak pada bagian hilir sungai Bogowonto sehingga menyebabkan banjir di beberapa lokasi terutama di sekitar Bandara Internasional Yogyakarta. Kapasitas aliran sungai Bogowonto yang semakin berkurang sehingga menimbulkan permasalahan banjir, sehingga penelitian ini perlu dilakukan suatu analisis. Analisis backwater di muara Sungai Bogowonto mensimulasikan jetty eksisting dalam program HEC-RAS. Sebaliknya, simulasi perubahan morfologi sungai dengan dua skenario jetty menggunakan program DELFT3D. Kata-kata Kunci: Sedimen, banjir, backwater, muara, jetty.